Evaluation of inpatient services of tertiary comprehensive hospitals based on DRG payment - Yu, Qun-jun; Li, Ya-lin; Yin, Qin; Lu, Ye; Li, Lu-yan; Xu, Dan-ni; He, Mei; Ma, Sha; Yan, Wu (Frontiers in Public Health, 2024)
Objective This study aims to evaluate inpatient services in 49 tertiary comprehensive hospitals using indicators from the diagnosis related groups (DRG) payment system. Method DRG data from 49 tertiary comprehensive hospitals were obtained from the quality monitoring platform for provincial hospitals, and relevant indicators were identified. The analytic hierarchy process (AHP) was used to compute the weight of each indicator. The rank sum ratio method was used to calculate the weight rank sum ratio (WRSR) value and the corresponding probit value of each hospital. The hospitals were divided into four grades based on the threshold value: excellent, good, fair, and poor. Results Eight indicators of the 49 hospitals were scored, and the hospital rankings of indicators varied. The No. 1 hospital ranked first in the indicators of “total number of DRG”, “number of groups”, and “proportion of relative weights (RW) ≥ 2”. The WRSR value of the No.1 hospital was the largest (0.574), and the WRSR value of the No. 44 hospital was the smallest (0.139). The linear regression equation was established: WRSRpredicted =-0.141+0.088*Probit, and the regression model was well-fitted (F = 2066.672, p < 0.001). The cut-off values of the three WRSRspredicted by the four levels were 0.167, 0.299, and 0.431, respectively. The 49 hospitals were divided into four groups: excellent (4), good (21), average (21), and poor (3). There were significant differences in the average WRSR values of four categories of hospitals (p < 0.05). Conclusion There were notable variances in the levels of inpatient services among 49 tertiary comprehensive hospitals, and hospitals of the same category also showed different service levels. The evaluation results contribute to the health administrative department and the hospital to optimize the allocation of resources, improve the DRG payment system, and enhance the quality and efficiency of inpatient services.